Decision-Making by Patients With Methamphetamine Use Disorder Receiving Contingency Management Treatment: Magnitude and Frequency Effects - Lake, Marilyn T.; Shoptaw, Steven; Ipser, Jonathan C.; Takada, Sae; van Nunen, Lara J.; Lipinska, Gosia; Stein, Dan J.; London, Edythe D. (Frontiers in Psychiatry, 2020)
Abstract Background: Individuals with substance use disorders exhibit maladaptive decision-making on the Iowa Gambling Task (IGT), which involves selecting from card decks differing in the magnitudes of rewards and the frequency and magnitude of losses. We investigated whether IGT performance could predict responses to Contingency Management (CM) by treatment-seeking individuals with Methamphetamine Use Disorder in Cape Town South Africa. Methods: Twenty-nine individuals with Methamphetamine Use Disorder underwent an 8-week, escalating reinforcement, voucher-based CM treatment in a study on the suitability of CM therapy for the South African context. Along with 20 healthy control participants, they performed a computerized-version of the IGT before starting CM treatment. Seventeen participants maintained abstinence from methamphetamine throughout the trial (full responders), and 12 had an incomplete response (partial responders). Performance on the IGT was scored for Magnitude Effect (selection of large immediate rewards with high long-term loss) and for Frequency Effect (preference for frequent rewards and avoidance of frequent losses). Group differences were investigated using linear mixed-effect modelling. Results: Partial responders made more selections from decks providing large, immediate rewards and long-term losses than healthy controls (p=0.038, g=-0.77[-1.09: -0.44]). Full responders showed a greater, non-significant, preference for frequent rewards and aversion to frequent losses than partial responders (p=0.054, g =-0.63 [-0.95: -0.29]). Conclusions: A predilection for choices based on the size and immediacy of reward may reflect a cognitive strategy that works against CM. Pre-testing with a decision-making task, such as the IGT, may help in matching cognitive therapies to clients with Methamphetamine Use Disorder.